Internal transcribed spacer (ITS) sequence-based identification of yeast biota on pomegranate surface and determination of extracellular enzyme profile - Tülay Turgut Genç; Melih Günay (Nusantara Bioscience, 2020)
Abstract. Genc TT, Günay M. 2020. Internal transcribed spacer (ITS) sequence-based identification of yeast biota on pomegranate surface and determination of extracellular enzyme profile. Nusantara Bioscience 12: 59-67. Yeasts are the most significant organisms to produce fermented products from different types of fruits such as grape, strawberry and pomegranate. The native yeasts on these fruits contribute to beverages’ quality and aroma during fermentation. Pomegranate is used in fruit juice and wine production because of high antioxidant characteristic. In order to determine yeast microbiota on the pomegranate fruits collected from Gallipoli (Gelibolu), Çanakkale-Turkey, ITS-5.8S rDNA gene region have been utilized. Also, phylogenetic relationships among identified yeast species were assigned by using sequences of ITS-5.8S rDNA gene region. In addition, extracellular enzyme activity of identified yeast strains was detected by using API-ZYM. Kluyveromyces lactis, Aureobasidium pullulans, Hanseniaspora uvarum, Candida zeylanoides, Kwoniella sp., and Metschnikowia pulcherrima and Metschnikowia ziziphicola yeast species were identified on pomegranate surface. Phylogenetic analysis, carried out in ITS-5.8S rDNA gene region of identified yeast strains, revealed the presence of five clades. Kwoniella sp., H. uvarum, M. pulcherrima, and Kl. lactis yeast strains revealed high leucine arylamidase activity. Also valine arylamidase activity was determined in M. pulcherrima and Kl. lactis yeast species. Acid phosphatase activity was determined in H. uvarum and K. lactis yeast species. Uncultured Kwoniella sp. and H. uvarum yeast species displayed high ?-galactosidase and ?-glucosidase activities, respectively.